The motogenic effect of EGF and TGF-α on the migration of tumor cells from the oral region: A role of epithelial-to-mesenchymal transition in cancer and a route for translation into the clinic. (21st March 2017) - Islam, Mohammad; Mane, Shraddha; Hyder, Erum; Jones, Sarah; Ellis, Ian
Aim: Epithelial-to-mesenchymal transition (EMT) is recognized as a hallmark of cancer. The change in phenotype of epithelial cells enables them to migrate and the cancer therefore, to become more aggressive. The presence of the epidermal growth factor receptor (EGFR) has been implicated in the spread and aggressive nature of oral tumors. The aims of this present study were to investigate the role of two different growth factors, both ligands of the receptor, and their influence on EMT and cellular motility. Methods: A number of assays were used to investigate the response of the cells to the two growth factors (EGF and transforming growth factor (TGF-α)). These techniques included the 2-D scratch assay, a 2-D-cell scatter assay, and immunocytochemistry. Normal keratinocytes (HaCaT), oral adenoid squamous cell carcinoma (TYS), and human salivary gland tumor cells were used in this study. Results: The results of the scratch and scatter assays indicated that EGF and TGF-α exerted differential effects upon the cells. EGF and TGF-α stimulated the migration of cancer cells in scratch assays. Scatter assays have revealed that both EGF and TGF-α induce EMT. EGF- and TGF-α-induced scattering is EGFR dependent and localization of EMT markers (E-cadherin and vimentin) might play an important role in scattering. These responses were also found to be dependent upon cell type, indicating that the assay could also be used as a simple screen for active growth factor. The observed effects were also dose dependant (data not shown). Conclusion and implication for translation to clinic: We have previously reported that although EGF and TGF-α have ultimately similar effects on motility, it would appear that different mechanisms are responsible. This data extends our knowledge of the action of these growth factors to epithelial cell lines and will inform future testing of the effects of EGF and TGF-α inhibitors.